2019
DOI: 10.3390/dj7010021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fixed Orthodontic Treatment on Salivary Nickel and Chromium Levels: A Systematic Review and Meta-Analysis of Observational Studies

Abstract: Nickel and chromium ions released from fixed orthodontic appliances may act as allergens. This study aimed to systematically review the effect of fixed orthodontic treatment on salivary levels of these ions by doing a meta-analysis on cross-sectional and cohort studies. The Web of Science, Scopus, Cochrane Library, and PubMed databases were searched for articles on salivary profile of nickel or chromium in patients under fixed orthodontic treatment published from January 1983 to October 2017. A random-effect m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
(68 reference statements)
1
12
0
Order By: Relevance
“…Nickel is the most common metal that causes contact dermatitis and induces more cases of allergic reactions. The amount of nickel as the main constituent of contemporary orthodontic appliances may vary from 8% in stainless steel to more than 50% in NiTi alloys [ 35 ]. However, in most of the in vivo studies that have evaluated the liberation of metal ions from orthodontic appliances in biological fluids, it has been concluded that levels of metal ions do not reach the normal daily dietary intake of some elements [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nickel is the most common metal that causes contact dermatitis and induces more cases of allergic reactions. The amount of nickel as the main constituent of contemporary orthodontic appliances may vary from 8% in stainless steel to more than 50% in NiTi alloys [ 35 ]. However, in most of the in vivo studies that have evaluated the liberation of metal ions from orthodontic appliances in biological fluids, it has been concluded that levels of metal ions do not reach the normal daily dietary intake of some elements [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are important clinical, in vivo studies that analysed patients' saliva and monitored nickel release from orthodontic appliances before and during orthodontic treatment [96][97][98]. The results from research in the years 1997 to 2016 on the concentration of Ni in patients' saliva in patients with fixed orthodontic treatment were summarized in meta-analysis study [97].…”
Section: Biocompatibility and Ni Releasementioning
confidence: 99%
“…Metal ions such as chromium (Cr) and nickel (Ni) are released into the oral cavity due to corrosion of the wires and brackets of fixed orthodontic appliances under numerous environmental conditions [ 1 ]. Additionally, several mouthwashes can influence the corrosion of metallic appliances and cause the release of Ni and Cr into patient’s saliva [ 2 ].…”
Section: Introductionmentioning
confidence: 99%